KNOWLEDGE OF SECONDARY SCHOOL STUDENTS ABOUT BASIC LIFE SUPPORT - Silva, Mafalda Sofia Gomes Oliveira da; Ferreira, Maria Margarida Silva Vieira; Rodrigues, Alexandre Marques; Sousa, Cláudia Noémia Soares de (Cogitare Enfermagem, 2024)
Objective: Evaluate high school students’ knowledge about basic life support and analyze the associations between the level of knowledge and sociodemographic and academic variables. Method: Quantitative, descriptive, cross-sectional, and correlational study. The sample consisted of 59 high school students from a Secondary School in the metropolitan area of Porto - Portugal. Descriptive analyses, Pearson’s correlation coefficient, and t test (or non-parametric tests when assumptions were not met) were used. Results: 35 (59.3%) had basic life support training, and 52 (88.1%) were interested in undergoing the training. Only seven (11.9%) were aware of an automatic external defibrillator and 14 (23.7%) identified when to seek specialized help. Conclusion: Knowledge about basic life support can contribute to achieving better outcomes in situations of cardiorespiratory arrest, and students should increase their skills in this area by using training in the school context.